Pengruh Profitabilitas, Pertumbuhan Aktiva, dan Struktur Aktiva Terhadap Keputusan Pendanaan Pada Perusahaan Others di BEI - Darmayanti, Ni Putu Mirah (E-Jurnal Manajemen, 2013)
Funding decisions are part of the financial decisions related to debt in a company. Funding decisions are influenced by many factors, such as profitability, asset growth, and asset structure. This study aimed to determine the effect of profitability, asset growth, and asset structure of the company's funding decisions on others in the Indonesia Stock Exchange the period 2008-2011. Sampling method used was purposive sampling. Testing method used is multiple linear regression analysis, F test and t test. The results of this study are profitability, asset growth, asset structure simultaneously and significantly influence funding decisions. Partially profitability and asset growth effect signifkan the funding decision, while the asset structure variables do not significantly influence funding decisions. Keywords: Financing Decision, Profitability, Asset Growth, Structure of Assets